Conceptualizing patient participation in psychiatry: A survey describing the voice of patients in outpatient care - Rikard Wärdig; Fredrik Olofsson; Ann Catrine Eldh (Wiley, 2021)
Abstract Background While increasingly discussed in somatic care, the concept of patient participation remains unsettled in psychiatric care, potentially impeding person‐centred experiences. Objective To describe outpatient psychiatric care patients' conceptualization of patient participation. Design An exploratory survey. Setting and participants Patients in four psychiatric outpatient care units. Variables Patients conceptualized patient participation by completing a semi‐structured questionnaire, including optional attributes and free text. Data were analysed using statistics for ordinal data and content analysis for free text. Results In total, 137 patients (69% of potential respondents) completed the questionnaire. The discrete items were favoured for conceptualizing patient participation, indicating a primary connotation that participation means being listened to, being in a reciprocal dialogue, learning about one's health care and managing one's symptoms. Additional free‐text responses acknowledged the attributes previously recognized, and provided supplementary notions, including that patient participation is about mutual respect and shared trust. Discussion What patient participation is and how it can be facilitated needs to be agreed in order to enable preference‐based patient participation. Patients in outpatient psychiatric care conceptualize participation in terms of both sharing of and sharing in, including taking part in joint and solo activities, such as a reciprocal dialogue and managing symptoms by yourself. Conclusion While being a patient in psychiatric care has been associated with a lack of voice, an increased understanding of patient participation enables person‐centred care, with the benefits of collaboration, co‐production and enhanced quality of care. Patient contribution Patients provided their conceptualization of patient participation in accordance with their lived experience.